2002
DOI: 10.1071/mf01082
|View full text |Cite
|
Sign up to set email alerts
|

Settlement behaviour of coral-reef fish larvae at subsurface artificial-reef moorings

Abstract: Artificial-reef units (rolls of plastic garden mesh) attached to subsurface floats were used to study settlement behaviour of larval reef fishes. These units were located 3, 5, 7 and 9 m above the bottom in water 15–19 m deep in the Great Barrier Reef Lagoon, 1 km from natural reefs. Larvae of 50 species (15 families) settled on these units. The nine most abundant reef-fish taxa were in the families Apogonidae, Blenniidae, Gobiidae, Monacanthidae, Pomacentridae and Tetraodontidae. The less abundant of these ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…These studies used sampling intervals smaller than the present study: 4 to 10 days (Schroeder, 1987), 2 days (Leis et al, 2002) and 7 days (Paiva et al, 2015), in addition to different positioning arrays and abundance calculations. Leis et al (2002) computes the sample mean just for the FADs in which individuals of were found, while Schroeder (1987) calculates the abundance in recruits/FAD/day. On the other hand, authors like Paiva et al (2015) do not report catches by FADs, just the total number of individuals per species per treatments.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These studies used sampling intervals smaller than the present study: 4 to 10 days (Schroeder, 1987), 2 days (Leis et al, 2002) and 7 days (Paiva et al, 2015), in addition to different positioning arrays and abundance calculations. Leis et al (2002) computes the sample mean just for the FADs in which individuals of were found, while Schroeder (1987) calculates the abundance in recruits/FAD/day. On the other hand, authors like Paiva et al (2015) do not report catches by FADs, just the total number of individuals per species per treatments.…”
Section: Discussionmentioning
confidence: 94%
“…The low efficiency of ARM model, compared to the SMURF, was unexpected, since several studies with ARM achieved relatively high recruits' catches (Schroeder, 1987;Leis et al, 2002;Paiva et al, 2015). These studies used sampling intervals smaller than the present study: 4 to 10 days (Schroeder, 1987), 2 days (Leis et al, 2002) and 7 days (Paiva et al, 2015), in addition to different positioning arrays and abundance calculations. Leis et al (2002) computes the sample mean just for the FADs in which individuals of were found, while Schroeder (1987) calculates the abundance in recruits/FAD/day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations